Little Mamá forgets - Cruise, Robin, 1951- (Farrar, Straus and Giroux, 2006)
Although her Mexican-American grandmother now forgets many things, Luciana finds that she still remembers the things that are important to the two of them. Includes glossary of Spanish words used.